A Pediatric Food Allergy Support Group Can Improve Parent and Physician Communication: Results of a Parent Survey. (10th October 2011) - Sharma, Ashika; Prematta, Tracy; Fausnight, Tracy
Abstract : Rationale . We sought to evaluate the impact of having an allergist at a food allergy support group (FASG) on the relationship between parents and their child's allergist. Methods . Ninety-eight online surveys were sent to parents who attend a FASG affiliated with our institution. Responses were analyzed looking for reasons for attending the support group and comfort with having an allergist present at the meetings. The main objective of this study was to evaluate the impact of having an allergist at the food allergy support group on the relationship between parents and their child's allergist. Results . The FASG decreased anxiety about food allergies for 77.7% of those who responded. Most (71.4%) felt the FASG improved their child's quality of life. Greater than 90% felt comfortable having an allergist at the support group meeting, and 64.3% felt that talking to an allergist at the FASG made it easier to speak with their child's allergist. Conclusions . FASG meetings appear to be a good way for families of children with food allergies to learn more about food allergies, improve quality of life, and increase comfort in communicating with a child's allergist.